Evaluation of combined Gd-EOB-DTPA and gadobutrol magnetic resonance imaging for the prediction of hepatocellular carcinoma grading. (August 2016) - Schelhorn, Juliane; Best, Jan; Dechêne, Alexander; Göbel, Thomas; Bertram, Stefanie; Lauenstein, Thomas; Kinner, Sonja
Background: Tumor biopsy is not essential for the diagnosis of hepatocellular carcinoma (HCC); however, grading remains important for the prognosis. Purpose: To investigate whether combined Gd-EOB-DTPA and gadobutrol liver magnetic resonance imaging (MRI) can predict HCC grading. Material and Methods: Thirty patients (66.6 ± 7.3 years) with histologically confirmed HCC (grade 1, n = 5; grade 1–2, n = 6; grade 2, n = 13; grade 2–3, n = 2; grade 3, n = 4) underwent two liver MRIs, one with gadobutrol and one with Gd-EOB-DTPA, on consecutive days. Blinded to grading, two radiologists reviewed the gadobutrol and Gd-EOB-DTPA images in consensus with respect to: (i) HCC hyper-/iso-/hypointensity in the arterial, portal-venous/delayed, and Gd-EOB-DTPA hepatocellular phase; and (ii) morphologic tumor features (encapsulated growth, vessel invasion, heterogeneity, liver capsule infiltration, satellite metastases). Results: A significant correlation with grading was not found for either the combined dynamic information of all gadobutrol phases (r = −0.187, P = 0.331) or all the Gd-EOB-DTPA phases (r = 0.052, P = 0.802). No correlation with grading was found for a combination of arterial and hepatocellular phase in Gd-EOB-DTPA MRI (r = 0.209, P = 0.305), a combination of both arterial phases (gadobutrol and Gd-EOB-DTPA) with the Gd-EOB-DTPA hepatocellular phase (r = 0.240, P = 0.248), or a combination of all available gadobutrol and Gd-EOB-DTPA phases (r = 0.086, P = 0.691). For all gadobutrol information (dynamic phases and morphology; r = 0.049, P = 0.801) and for all Gd-EOB-DTPA information (r = 0.040, P = 0.845), no correlation with grading was found. Hepatocellular Gd-EOB-DTPA phase iso-/hyperintensity never occurred in grade 3 HCCs. Conclusion: Histological HCC grading cannot be predicted by combined Gd-EOB-DTPA/gadobutrol MRI. However, Gd-EOB-DTPA hepatocellular phase iso-/hyperintensity was never detected in grade 3 HCCs.